Work experience internship of the students pursuing master’s degree in teacher education - Panova I.Е.Kharchenko L.N., Igropulo I.F., Klushinа N.P., Klushinа E.A., (Opción, 2020)
The study aims to investigate the role and place of work experience internship of the students pursuing a master’s degree in teacher education in the North Caucasus Federal University via analysis and abstracting of scientific, pedagogical and methodological literature. As a result, completing a graduate internship prepares master’s students for independent work in their chosen profession. In conclusion, constant modernization of the content of graduate internship is required in order to ensure the motivational, personal and technological readiness of the students in the master’s program in education for continuous and self-directed professional development.